Meningkatkan Motivasi Belajar Siswa Melalui Gamifikasi (Point, Badge, Leaderboard) Pada Pembelajaran Seni Rupa Di Kelas IV SDN 7 Telaga Kabupaten Gorontalo - Nadia Datunsolang; Sukri Katili; Mimy Astuty Pulukadang; Rustam I. Husain; Wiwy Triyanty Pulukadang (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aimed to improve the learning motivation of fourth-grade students at SDN 7 Telaga, Gorontalo Regency, in Visual Arts learning through the implementation of gamification based on points, badges, and leaderboards. The study employed Classroom Action Research using the Arikunto model, conducted in two cycles involving 18 students as research participants. Data were collected through observation, interviews, practical tests, and documentation, then analyzed descriptively based on four indicators of learning motivation. The results showed an increase in the number of students who achieved the proficient criteria, from 11% in the initial condition to 83% at the end of Cycle II. The implementation of gamification also encouraged students to participate more actively, complete tasks more persistently, and collaborate more effectively. These findings indicate that gamification based on points, badges, and leaderboards effectively improves students’ motivation, participation, persistence, and collaboration in elementary school Visual Arts learning